Efektivitas Pembelajaran PAI Berbasis Inkuiri Terhadap Pemahaman Materi Rasa Ingin Tahu dan Kemampuan Berpikir Analitis Siswa - Salwa Amalia Jaudah; Retno Widyaningrum (PT. Pusmedia Group Indonesia, 2024)
Islamic Religious Education does not only teach about students' cognitive abilities but also about the values and character of students. In its implementation, the teacher is an important factor in conveying this by using appropriate and appropriate learning methods. This study aims to analyze the effect of inquiry-based Islamic Religious Education (PAI) learning on material understanding, curiosity, and analytical thinking skills of students at SMP N 1 Kebonsari Madiun. This scientific work fully uses quantitative research methods. The research method used was an experiment with a pretest-posttest control group design. The research sample consisted of 35 students from class VIII A which was divided into an experimental group of 17 students and a control group of 18 students. This research was conducted using the SPSS formula among normality test, homogeneity test, and unpaired t test. The results showed that inquiry-based PAI learning significantly improved students' material understanding, curiosity, and analytical thinking skills compared to conventional methods. Keywords: PAI Learning; Inquiry Model; Analytical Thinking